TRADISI RASOL DALAM PERSPEKTIF ISLAM - Mahfud, Mahfud (INTAJ, 2018)
This article attempts to explain the Rasol tradition as the local cultural wisdom of the Buloar Society. The Rasol tradition is the heritage of the ancestors of the Buloar people from the adherents of dynamism and animism that eventually come into contact with established religions such as Hinduism, Buddhism, and then also in touch with Islam as a well-established religion that continues in the form of acculturation of Islamic face. The heritage of the ancestors is still preserved in the local culture that still runs in the form of rituals and symbols. Ritual becomes the framework of action to present and relate well to God arranged in a prayer as a way of expressing hope for salvation from all the efforts it undertakes, while symbols provide a way to express meaning through the media with certain symbols to show the sacred and profane meaning of the Rasol tradition. Rasol is a system that is lived by the community, preserved by the role of elite and community leaders, as well as the participation of the community members. This is recognized as local Islam in the local cultural wisdom of the people of Buloar. Keywords: Tradition, Rasol, Islamic perspective.